Implementasi Microsoft Excel Sebagai Media Pelatihan Analisis Keuangan - Ferdinando Solissa; Putu Anggreyani Widya Astuty; Margaretha Turot; Ignatz Novrian Fayliencent; Irwan Soulisa; Felisia Tesalonika Yarangga (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
This Community Service (PKM) activity is a continuation program conducted by the Accounting Study Program, Faculty of Economics and Business, Victory University Sorong. The activity aims to improve participants' abilities in utilizing Microsoft Excel as a financial analysis tool. The implementation method consisted of lectures, demonstrations, direct practice, and mentoring. Participants were introduced to basic Excel formulas such as SUM, AVERAGE, IF, SUMIF, and VLOOKUP, as well as financial ratio analysis and simple dashboard preparation. The results showed an increase in participants' understanding and skills in processing financial data using Microsoft Excel. This activity supports digital literacy development and prepares participants to face the demands of technology-based financial administration in education and the workplace.